REMONOR : Résultats 2003. Evaluation de la mortalité, croissance et qualité des huîtres creuses - Simonne, Charlotte; Pien, S.; Hugonnet, Virginie; Le Gagneur, Eric; Ropert, Michel; Kopp, Joel; Richard, O. (2004)
The network named REMONOR (REseau MOllusqueNORmandie) aims to assess mortality, growth and tissue quality of the Pacific oyster, Crassostrea gigas, cultivated in Normandy over an annual cycle. This local network relies on the same material and methods as the national one named REMORA (REseau Mollusques Ressources Aquacoles). The study was carried out in 17 sites, which were distributed in the four basins where oyster rearing occurs in Normandy (West and East coast of Cotentin, Baie des Veys and Meuvaines). In 2003, a new site was added, which was located in the area of Ver-Sur-Mer (Calvados). The results obtained in 2003 showed a low annual mortality for adults (8%) as well as for juveniles (10%). Growth was also low for the two age classes of oyster except for the sites of Lingreville (West coast of Cotentin), Le Lézard (Chausey) and Géfosse (Baie des Veys). The condition index, representative of tissue quality, increased regularly since 2000 whereas the level of oyster infestation by the worm Polydora remained stable. Le réseau régional de suivi Remonor s'appuyant sur les acquis du réseau national REMORA de l'Ifremer, évalue la mortalité, la croissance et la qualité des huîtres creuses. Depuis 1998, les points de suivi ne cessent d'augmenter puisqu'une nouvelle station vient d'être créer pour cette année 2003 sur la zone conchylicole de Ver-sur-Mer. Constitué de 17 stations réparties sur les quatre bassins ostréicoles bas-Normand, son objectif est de suivre annuellement deux classes d'âge, juvéniles et adultes, d'huîtres creuses. Les résultats 2003, montre une mortalité faible tant chez les adultes (8%) que chez les juvéniles (11%), une croissance peu importante pour les deux classes d'âges mis à part sur les stations de Lingreville (Côte Ouest), Le Lézard (Chausey) et Géfosse (Baie des Veys). L'indice de chair régional est en légère progression depuis l'année 2000 (11,4) et l'indice polydora reste stable.